2015
DOI: 10.1007/s10570-015-0723-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mechanical and morphological properties of cellulose reinforced polyamide 6 composites

Abstract: The utilization of cellulose in reinforcing engineering thermoplastics through melt compounding processes is an argumentative topic in the natural fiber research community. Three different cellulosic materials were used to reinforce polyamide 6 (PA6) at three loading levels (2.5, 5 and 10 % by weight): (1) microcrystalline cellulose, (2) spray-dried cellulose nanofibrils (CNFs) and (3) spray-dried cellulose nanocrystals (CNCs). The particle size, morphology, and thermostability of cellulose were determined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 30 publications
4
45
0
Order By: Relevance
“…[9][10][11][12] Carbon fibre is a synthetic fibre extensively used as a reinforcing agent in aerospace and automotive industries due to its low weight and excellent mechanical properties, including high stiffness and tensile strength and great chemical and thermal resistance. [25][26][27][28][29][30][31][32][33][34][35][36] However, use of these polymers as matrices for cellulosic fibres is challenging as their processing temperatures are above the degradation temperature of the cellulosic fibres. Many studies have reported that hybrid composites composed of natural and synthetic fibres can improve the mechanical and thermal properties of the composites by having the benefits of both fibre types while reducing the costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] Carbon fibre is a synthetic fibre extensively used as a reinforcing agent in aerospace and automotive industries due to its low weight and excellent mechanical properties, including high stiffness and tensile strength and great chemical and thermal resistance. [25][26][27][28][29][30][31][32][33][34][35][36] However, use of these polymers as matrices for cellulosic fibres is challenging as their processing temperatures are above the degradation temperature of the cellulosic fibres. Many studies have reported that hybrid composites composed of natural and synthetic fibres can improve the mechanical and thermal properties of the composites by having the benefits of both fibre types while reducing the costs.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] However, carbon fibre is non-renewable and energy intensive in its manufacture, and quite expensive compared to natural fibres. [25][26][27][28][29][30][31][32][33][34][35][36] Biopolyamides have relatively low melting temperature and are another suitable alternative to develop cellulosic fibre-reinforced composites with high-performance characteristics. [19][20][21][22][23] Polyamides are one of the most widely used engineering polymer matrices in the automotive industry.…”
Section: Introductionmentioning
confidence: 99%
“…We also concluded from the temperature corresponding to the first and the second peak of DTG curves ( T max ) in Table that the thermal stability of the polymer blends with CNCs was better than that with CNFs at the same content because of the immiscible interfacial modification. The CNC nanocomposites were assumed to show a much lower temperature at which the maximum mass loss rate occurred due to the sulfate groups from the CNCs during the manufacturing process . The influence of the miscible interface may have been dominant and should be placed ahead of other factors such as reinforcement.…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve the thermal stabilization of the natural fibers, there are some ways developed for the modification, for instance, sodium hydroxide solution treatment, thermal treatment, and plasma treatment . In addition, cellulose‐based materials with favorable heat resistance were also incorporated, such as microcrystalline cellulose, cellulose nanofibrils (CNFs), and cellulose nanocrystals . According to the previous reports, depressing the melting temperature of PA6 is another promising method.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] In addition, cellulose-based materials with favorable heat resistance were also incorporated, such as microcrystalline cellulose, cellulose nanofibrils (CNFs), and cellulose nanocrystals. [17][18][19][20] According to the previous reports, depressing the melting temperature of PA6 is another promising method. PA6/wheat straw composites was prepared via incorporating lithium chloride (LiCl).…”
Section: Introductionmentioning
confidence: 99%